Effects of spent mushroom substrate and slurry on nutritional value of grass and Medicago x varia T. Martyn mixtures - Jankowski, Kazimierz; Malinowska, Elżbieta; Sosnowski, Jacek; Wiśniewska-Kadżajan, Beata; Kaczorek, Anna (International Journal of Agricultural and Biological Engineering, 2018)
The paper aimed to evaluate fertilizing effects of spent mushroom substrate (SMS) and slurry on dry matter productivity and value of legume-grass mixtures. The experiment was replicated three times, with a split-plot arrangement and plots of 3 m3 as experimental units. These species were grown as three legume-grass mixtures: M1–Dactylis glomerata, Lolium perenne, Medicago x varia T. Martyn; M2– Dactylis glomerata, Medicago x varia T. Martyn; M3–Lolium perenne, Medicago x varia T. Martyn. The experiment consisted of the following units: control (no fertilization); SMS (30 t/hm2); slurry (60 m3/hm2) (G); SMS (10 t/hm2) + slurry (60 m3/hm2); SMS (20 t/hm2) + slurry (40 m3/hm2); SMS mushroom substrate (30 t/hm2) + slurry (20 m3/hm2). During each growing season all the mixtures were harvested three times. The fresh matter from each plot was weighted and a sample of 0.6 kg was taken for further analysis. In the experiment the content of both total protein and crude fibre was dependent on the type of fertilizer and on the type of mixture. Forage from the plots with 20 t/hm2 of mushroom substrate and 40 m3/hm2 of slurry had the best nutritional value, with the highest amount of total protein. The contents of protein and crude fibre in the forage were more favourably affected by slurry than by spent mushroom substrate. Out of the mixtures from all plots, regardless of the type of fertilizer, the mixture consisting of Lolium perenne and Medicago x varia T. Martyn contained the highest content of protein.Keywords: fertilizer, spent mushroom substrate, nutritional value, protein concentration, fibre concentrationDOI: 10.25165/j.ijabe.20181103.3726Citation: Kazimierz J, Elżbieta M, Jacek S, Beata W, Anna K. Effects of spent mushroom substrate and slurry on nutritional value of grass and Medicago x varia T. Martyn mixtures. Int J Agric & Biol Eng, 2018; 11(3): 61–66.